1980
DOI: 10.1073/pnas.77.3.1588
|View full text |Cite
|
Sign up to set email alerts
|

Discrete stages of human intrathymic differentiation: Analysis of normal thymocytes and leukemic lymphoblasts of T-cell lineage

Abstract: A series of monoclonal antibodies was used to define three discrete stages of human intrathymic T-cell differentiation. The earliest stage was confined to <10% of thymocytes, which were.reactive with both OKT9 and OKT1O. Subsequently, approximately 70% of human thymocytes acquired a thymocyte-restricted antigen, OKT6, lost OKT9 antigen, and expressed reactivity with OKT4 and OKT5. These last two monoclonal antibodies were previously shown to define inducer (helper) and cytotoxic/suppressor populations, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
440
0
5

Year Published

1980
1980
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,424 publications
(461 citation statements)
references
References 22 publications
16
440
0
5
Order By: Relevance
“…The observation that CD8 þ T cells expressing only HLA-DR but not CD38 are lost in Ethiopian AIDS patients is in agreement with a previous prospective study which demonstrated that the presence of this subset is associated with long-term survival and stable CD4 þ T cell counts [14]. Apart from being an activation marker, CD38 is also detected in immature cells [43].The representation of CD4 þ and CD8 þ T cells expressing only CD38 but not HLA-DR is increased in both HIV þ and AIDS groups compared with the HIV ¹ group. This observation may reflect that in HIV infection, apart from immune activation, there is also an increased flow of immature cells into the periphery due to accelerated destruction and replacement of mature T cells (see also [44]).…”
Section: Discussionsupporting
confidence: 91%
“…The observation that CD8 þ T cells expressing only HLA-DR but not CD38 are lost in Ethiopian AIDS patients is in agreement with a previous prospective study which demonstrated that the presence of this subset is associated with long-term survival and stable CD4 þ T cell counts [14]. Apart from being an activation marker, CD38 is also detected in immature cells [43].The representation of CD4 þ and CD8 þ T cells expressing only CD38 but not HLA-DR is increased in both HIV þ and AIDS groups compared with the HIV ¹ group. This observation may reflect that in HIV infection, apart from immune activation, there is also an increased flow of immature cells into the periphery due to accelerated destruction and replacement of mature T cells (see also [44]).…”
Section: Discussionsupporting
confidence: 91%
“…Our results also confirm previous studies showing that in most cases of NHL a monoclonal LC expression of membraneassociated Ig (mlg; K or A) can be detected in frozen sections (Levy et al, 1977;Warnke & Levy, 1978) (Nathwani et al, 1978), w-hich reveals little about the malignant nature of the transformed tumour. Furthermore, the observations support previous reports (Habeshaw et al, 1979;Warnke & Levy, 1978) that in follicular (cent,roblastic-centrocytic) Further studies (with antibodies detecting T-cell subsets of helper and suppressor fuLnctions (Reinherz et al, , 1980) will reveal the clinical significance of these findings. Our data here show that these studies are technicallv feasible.…”
Section: Discussionsupporting
confidence: 88%
“…6). Other monoclonal antibodies reacting with T cells , T-cell subsets (Reinherz et al, , 1980, B cells and B cell subsets (Brooks et al, 1980) will further advance the immunological analysis of NHL, especially if used in appropriate combinations with other anitisera. The use of a panel of antibodies against B-cell subsets would be important, since the analysis of receptor profiles on these subsets already reveal remarkable (but not absolute) correlations with the histological pattern of NHL, and show prognostic significance (Habeshaw et al, 1979;Stein et al, 1978).…”
mentioning
confidence: 99%
“…In addition to CD7 and cCD3, Pre-T ALL cases express surface CD2, CD5, and/or CD8. As cortical thymocytes (41), leukemic cells from cortical T-ALL display reactivity for CD1a. The TIV/mature T-ALL phenotype (sCD3ϩ, CD1aϪ, CD4ϩ, or CD8ϩ) is more often observed among patients presenting with T-lymphoblastic lymphomas than a pure T-ALL.…”
Section: Immunophenotyping Of Acute Leukemias Contribution Of Immunopmentioning
confidence: 99%